Features of the produce organization of radio-electronic products (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2010)
Economic indicators that characterize the statistical quality control are considered. It is shown that achieving high quality appropriate to refuse access control, ensuring the consumer replenishment supplied a lot of products with additional products or properly organized maintenance products in during exploitation.